The Interference of Banjarese Dialect on English Pronunciation - Sunanda Alam Muliawan; Iwan Fauzi; Dellis Pratika; Sonia Vriska Yulinda Jami; Hikmal Maulana Nasution (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This study investigates the influence of the Banjarese dialect on the English vowel pronunciation of two Banjarese speakers. The research is grounded in the understanding that English and Banjarese differ substantially in their vowel inventories and rhythmic structures, which may lead to systematic phonological transfer. Using a qualitative case study approach combining Praat-based acoustic phonetic analysis and narrative inquiry, this study recorded two male Banjarese speakers aged 20 pronouncing selected English words containing problematic vowels (/æ/, /?/, /?/, /u?/, /??/). The recordings were analyzed to identify deviations in vowel quality and centralization, while semi-structured interviews explored speakers' awareness of and challenges with these qualities. The findings revealed consistent substitution patterns such as /æ/?/e/, /?/?/e/ or /i/, and /?/?/i/, accompanied by fronting and the absence of vowel reduction in unstressed syllables. These patterns reflect the influence of the Banjarese vowel system, which lacks central vowels, tense-lax contrasts, and vowel length distinction. Acoustic evidence confirmed the persistence of full vowel quality, indicating syllable-timed rhythm interference. The study supports Flege's Speech Learning Model and Best and Tyler's Perceptual Assimilation Model by demonstrating dialect-specific phonemic transfer. Pedagogically, the results suggest that explicit instruction on vowel reduction, centralization, and rhythm awareness may help mitigate Banjarese interference in English pronunciation.